(untitled) (Al-Academy, 2023)
In the 20th century, the concept of "sarcasm" has relatively prevailed, and in this sense, it is a method in the art of conversation that wants to keep the question about the intended meaning, that is, "saying something and suggesting its opposite." There are other concepts that indicate that sarcasm is saying something in a way that provokes the recipient of the statement an infinite number of different interpretations, with multiple readers of different interpretations. While the philosophy of irony stands by the standards of things, exaggeration or minimization, this manipulation takes place within the enjoyment. However, it’s a method to present sharp criticism in an atmosphere of criticism that differs from generation to generation and varies from artist to artist. Satirical art is a black comedy that reflects human pains and confusion and the phenomena of his life, and the satirical artist is the one who turns pain into astonishment and wants it to reach as a message. There are many contemporary artists who dealt with irony in social, economic, political and other topics. Therefore, the research aimed to reach some of the applications that it proposes for contemporary arts. It helps art students and specialists in its aesthetics to see the subject of irony that expands in its emerging methods